"Here if you need me": exploring peer support to enhance access to physical health care. (4th July 2018) - Bocking, Julia; Ewart, Stephanie B.; Happell, Brenda; Platania-Phung, Chris; Stanton, Robert; Scholz, Brett
Abstract: Background : People diagnosed with mental illness (hereinafter "consumers") have higher rates of chronic disease and significantly shorter lives than the wider population. Peer workers have become increasingly involved in facilitating access to physical health care, yet the consumer perspective regarding peer involvement is unknown. This absent voice is needed to inform strategic planning and generate solutions to address the current inequity in health status. Aim: To articulate the views of consumers in regards to the potential use of peer workers to further the physical health of people with mental illness. Methods : A qualitative exploratory study was conducted involving four focus groups with 31 consumer participants. Focus group responses were analysed thematically. Results : Three themes pertaining to enhancing physical health care emerged: (1) the potential of peer workers in mitigating existing barriers, (2) consumer advocacy organisations expanding their agenda and (3) benefits of segregated activities as a segue to mainstream options. Conclusions : The envisaged forms of peer contribution have far greater scope and depth than is currently considered in policy, the research literature and health practice. Innovative solutions are required for this neglected population. Individual and systemic advocacy led by peer workers can enhance access to physical health care and have the potential to reduce physical health inequalities.